Pengaruh Edukasi Gizi dengan Media E-Modul terhadap Pengetahuan, Sikap, dan Perilaku Gizi pada Remaja Overweight dan Obesitas di SMP Negeri 3 Tasikmadu - sahihsinda kurnia ardita; Setyo Prihatin; Susi Tursilowati; Yuniarti Yuniarti; Meirina Dwi Larasati (Poltekkes Kemenkes Semarang, 2022)
Background : Overweight and obesity are risk factors for chronic disease in adulthood. Factors that affect problem of overnutrition is level of knowledge. The national prevalence of overnutrition in adolescents aged 13-15 years has increased since 2013 to 2018. Objective: To determine effect of nutrition education with e-module media on knowledge, attitudes, nutritional behavior of overweight and obese adolescents. Methods: This is a nutrition science research with a quasi-experimental type of research and a pretest-posttest control group design. The number of respondents in each group amounted to 21 respondents. Research time for 4 weeks. The data collected are knowledge, attitudes, nutritional behavior through filling out questionnaire with an online google form. The knowledge and attitude forms each consist of 20 nutrition questions. Nutritional behavior using Qualitative FFQ form. Statistical analysis using Independent t-test, Mann-Whitney Test, Linear Regression. Results : There is an effect of nutrition education with e-module on nutrition knowledge (p 0.05); nutritional attitude in the first, third, fourth week (p 0.05); and nutrition frequency of consumption all risk foodstuffs causing excess nutrition (p 0.05) except for group of foods that are fat sources and their processed products (p 0.05). Conclusion : There is an effect of nutrition education with e-module media on nutrition knowledge and attitudes. There is no effect of nutrition education with e-module media on the nutritional behavior of the group of foodstuffs with fat sources and their processed products.